2005
DOI: 10.1002/ejoc.200400799
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Biological Evaluation of a Heparin‐Like Hexasaccharide with the Structural Motifs for Binding to FGF and FGFR

Abstract: A heparin-like hexasaccharide structure (2) containing the two trisaccharide sequences that interact with acidic fibroblast growth factor (FGF-1) and with its receptor (FGFR) has been designed on the basis of crystallographic data. This hexasaccharide has been effectively synthesized by a completely stereoselective modular approach and biologically

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
23
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 46 publications
(24 citation statements)
references
References 36 publications
1
23
0
Order By: Relevance
“…18 We have found that the structure of the hexasaccharide 1 has the same overall features as the previously studied heparin-like oligosaccharides, a rigid linear structure due to the geometry of the glycosidic linkages driven by the electrostatic repulsions between the charges of the sulphate groups. [14][15][16][17] In particular, it is very close to the structure of 2 that has remarkable mitogenic activity mediated by FGF-1 and shares many of its structural characteristics with the nonsymmetrical distribution of the sulphate groups on both sides of the molecule.…”
Section: Discussionsupporting
confidence: 64%
See 4 more Smart Citations
“…18 We have found that the structure of the hexasaccharide 1 has the same overall features as the previously studied heparin-like oligosaccharides, a rigid linear structure due to the geometry of the glycosidic linkages driven by the electrostatic repulsions between the charges of the sulphate groups. [14][15][16][17] In particular, it is very close to the structure of 2 that has remarkable mitogenic activity mediated by FGF-1 and shares many of its structural characteristics with the nonsymmetrical distribution of the sulphate groups on both sides of the molecule.…”
Section: Discussionsupporting
confidence: 64%
“…1). [14][15][16][17][18] The heparin regular region is made of repetitions of the D-GlcN-L-IdoA disaccharide, connected by α(1-4) linkages, with sulphate groups at positions 6 and 2 of glucosamine, and 2 of iduronate. In previous reports from our group, we have studied the activation of the mitogenic activity mediated by FGF-1 analysing the three-dimensional structure and dynamics of several hexa-and octasaccharides differing in their substitution pattern.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations